Keefektifan Pendekatan Konseling Behavioristik Dengan Teknik Role Playing untuk Mengurangi Perilaku Agresi Peserta Didik - Mita Yustika Putri (Universitas PGRI SUMATERA BARAT, 2019)
This research is motivated by students who behave aggressively. The purpose of this research is to: 1) Describe the behavior of students ' aggression before the behavioural counseling approach was conducted with role playing techniques; 2) Describe the aggressive behavior of students after an behavioural counseling approach with role playing techniques. 3) test the effectiveness of the behavioural counseling approaches with role-playing techniques to reduce the aggressive behavior of students. This research is experimental research. The population of this research is all students of Class XI Tata Niaga 1st SMK Negeri 1 Lubuk Sikaping, regency of Pasaman, amounting to 30 people. For sampling using purposive sampling technique. The number of samples in this study was 7 people gained through pretest results. The instruments used are questionnaires, data analyzed by percentages, and test T. Research findings: 1) descriptive behavior of aggression of students before behavioral counseling approach with role playing techniques are in aggressive category 2) descriptive Student aggression behaviour after behavioristic counseling approaches with role-playing techniques are in a non-aggressive category. 3) There is a decline in aggression behavior by using behaviorical counseling with role playing techniques. Based on the recommendation to students so they can reduce their aggression behavior on themselves so that they can live a social life well.